(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SUMMARY: 1. Introduction. Object of the evaluation: description of the exhibit – 2. Main part. An evaluation - 2.1. Communicative technique of combining the sacred with the low and vulgar associated with homosexual acts and the corresponding semantics condemned in the traditional Catholic religion - 2.2. Communicative technique of metonymic replacement (substitution) of one sign with another - 3. Conclusions.